Optimisation of the role of families of chronic hypertension patients based on the mcmaster model of family functioning in self-care agency - Proboningsih, Jujuk; Sriyono, Sriyono; Ambarwati, Rini; Wuryaningsih, Sri Hardi; Joeliantina, Anita (Jurnal Ners, 2025)
Introduction: This study aims to analyse the impact of the McMaster Model of Family Functioning (MMFF) on the self-care agency of patients with chronic hypertension in Surabaya. Methods: This study employs an analytical observational design with a cross-sectional approach, involving 300 respondents from families of patients with hypertension who meet the inclusion criteria. The independent variables examined include the six dimensions of the McMaster Model of Family Functioning (MMFF): problem-solving, communication, family roles, affective responsiveness, affective involvement, and behaviour control. Meanwhile, the dependent variable is self-care agency, which consists of medication, physical activity, and diet. Hypothesis testing was conducted using SEM-PLS, which was processed with SmartPLS 4.0.4 software. Results: The analysis results indicate that the MMFF has a positive and significant effect on self-care agency, with a coefficient of 0.340 (CI = 0.247 – 0.445). The effect size result obtained an effect size value of 0.131. Structured and adaptive family support, particularly in communication and affective involvement, has enhanced patients' motivation to adhere to medication and engage in self-care activities. Conclusions: This study expands on previous research on the role of family support in self-care agencies, by involving the McMaster Family Function Model (MMFF) to analyse the specific role of family functions in improving self-care agencies in chronic hypertension patients, thus providing a more comprehensive, contextual, and relevant perspective for family-based interventions. These results also enrich other theoretical studies, namely the Family-Centred Care (FCC) Model, Social Support Theory, and Health Belief Model (HBM).